Profile of Student’s Mathematical Connection in Arithmetic Sequences and Series Based on Learning Styles - Dyah Ayu Shofa Noer Azizah; Siti Khabibah; Dini Kinati Fardah (MATHEdunesa, 2023)
Mathematical connection is the linkage between mathematical concepts internally and externally. Internally, namely the linkage between the mathematical concepts themselves. Externally, namely the linkage between mathematical concepts with other disciplines and everyday life. This study aims to describe the profile of students' mathematical connections with visual, auditory and kinesthetic learning styles in the material of arithmetic sequences and series. The research subjects were students of class XI MIPA consisting of one student with a visual learning style, one student with an auditory learning style and one student with a kinesthetic learning style. The criteria for research subjects in this study were that they were of the same gender and had high and equal scores on mathematical ability tests. The research instruments consisted of a Learning Style Questionnaire, Mathematical Ability Test, and Mathematical Connection Test. The research method used in this research is descriptive qualitative. The indicators in this study refer to three aspects of mathematical connections, namely connections between mathematical concepts, connections between mathematical concepts with everyday life, and connections between mathematical concepts with other disciplines. Based on the analysis used, the results of this study are as follows: student with a visual learning style fulfill all indicators on all three aspects of mathematical connection. Student with a auditory learning style fulfill all indicators on all three aspects of mathematical connection. Student with a kinesthetic learning style doesn’t fulfill one indicator on the connection aspect between mathematical concepts, namely using the connection of mathematical concepts in solving question of arithmetic sequences and series, fulfill the indicator on the connection aspect between mathematical concepts with everyday life, fulfill the indicator on the connection aspect between concepts mathematics with other disciplines, but didn’t arrive to a final solution.